Problems Faced by the Third Semester Students of English Education Study Program in Listening Skills at Muhammadiyah University Of Palu: Masalah-Masalah yang Dihadapi Mahasiswa Semester Tiga Program Study Pendidikan Bahasa Inggris dalam Kemampuan Mendengarkan di Universitas Muhammadiyah Palu - Lisnia Devi; Nadrun; Ernitasari Mulyadi (Jurnal Kolaboratif Sains, 2022)
The purpose of this research is to investigate the listening problems faced by the third semester students of English Education Study Program at Muhammadiyah University Palu. This research applied descriptive research method. The subject was the third semester students of English Education Study Program at Muhammadiyah University Palu. The number was seven students. The data of the research were collected through a questionnaire, interview, and observation check list. The result of this research indicates that the students faced problems; (1) they get difficulty to determine the main idea and details information; (2) they are lack of vocabulary; (3) they are less initiative to read; (4) they get difficulty with speaker’s accent; (5) they get less focus; (6) they have less motivation to express themselves.